ISOLATION, CHARACTERIZATION AND SCREENING FOR ANTICANCER PROPERTY OF SEDIMENT DERIVED ACTINOMYCETES FROM SOUTH EAST COAST OF INDIA - S. SUDHA SRI KESAVAN, (International Journal of Pharma and Bio Sciences, 2015)
In the screening for actinomycetes with anticancer property, fifty two isolates were isolated using a starch casein agar medium from twenty marine sediment samples collected from the southeast coastal regions of India. Ten morphologically different isolates were selected and screened for cytotoxic active isolate by Brine shrimp lethality assay. One of the most potent isolate was selected for identification up to species level based on chemotaxonomic, cultural, physiological, biochemical analysis, and 16S rRNA gene sequencing. The ethyl acetate crude extracts of the identified isolate was analyzed by FT-IR and was subjected to MTT assay. The crude extract exhibited anticancer activity towards MCF-7 and HeLa cell lines with the IC50 of 19.95 and 25.1 µg/ml respectively and cytotoxic towards the VERO cell lines with the IC50 of >199.5µg/ml. The results of the present study revealed that the tentatively identified isolate Streptomyces globisporous strain SU7 could be pursued as a promising agent for the development of therapeutic anticancer drugs.